2016
DOI: 10.11646/zootaxa.4061.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Hesperus rougemonti sp. n. (Coleoptera, Staphylinidae) from Borneo

Abstract: The genus Hesperus Fauvel is, in its current concept, an obviously polyphyletic assemblage. One of the species groups that stand out, due to a combination of characters unusual for Hesperus, is the borneensis group. These characters are the subserrate antennae and the paramere bearing numerous peg setae. Otherwise, the members of this group look as typical for a Hesperus as it can be. At present, the group comprises the following species: H. birmanus Cameron, 1932, H. borneensis Bernhauer, 1915, H. javanus Cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…(A. F. Newton, unpublished database). Except Neobisnius , the monophyly of Philonthus , Gabrius , Bisnius , Gabronthus (Smetana, ; Solodovnikov and Schomann, ; Chani‐Posse, ), Belonuchus , Hesperus (Schillhammer, , ; Li and Zhou, ; Chani‐Posse, ), Cafius (Jeon et al., ) and Paederomimus (Chani‐Posse, ) has been questioned. Current diagnoses for those genera are based on a combination of plesiomorphies for Philonthina involving the structure of front tarsi (sexually dimorphic or not), pronotum (superior marginal line distinctly deflected or not, position of the lateral puncture relative to the superior marginal line), last segment of maxillary and labial palpi (shape and length), mesoventrite (transversely carinate or not, shape of apical portion), hind tarsi (relative length of tarsomeres 1 and 5) and sternum 9 (basal portion symmetric or asymmetric).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(A. F. Newton, unpublished database). Except Neobisnius , the monophyly of Philonthus , Gabrius , Bisnius , Gabronthus (Smetana, ; Solodovnikov and Schomann, ; Chani‐Posse, ), Belonuchus , Hesperus (Schillhammer, , ; Li and Zhou, ; Chani‐Posse, ), Cafius (Jeon et al., ) and Paederomimus (Chani‐Posse, ) has been questioned. Current diagnoses for those genera are based on a combination of plesiomorphies for Philonthina involving the structure of front tarsi (sexually dimorphic or not), pronotum (superior marginal line distinctly deflected or not, position of the lateral puncture relative to the superior marginal line), last segment of maxillary and labial palpi (shape and length), mesoventrite (transversely carinate or not, shape of apical portion), hind tarsi (relative length of tarsomeres 1 and 5) and sternum 9 (basal portion symmetric or asymmetric).…”
Section: Discussionmentioning
confidence: 99%
“…Although Smetana () found that the six Nearctic species of Hesperus formed a natural group, he recognized that characters defining this group ‘may pose difficulties for specimens from tropical areas, particularly from New Guinea, due to certain variability and/or absence of some character states’. Schillhammer () also noticed that characters defining Hesperus were not enough to clearly define the genus and considered it to be ‘a polyphyletic assemblage’ (Schillhammer, ). Still, he decided to maintain that concept until a revision covering at least the Palaearctic and Oriental regions is achieved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations